Publication trends on proportional reasoning research: A bibliometric analysis using Scopus database - Sugiarni, Rani; Abdullah , Khairul Hafezad (Universitas Terbuka, 2024)
Proportional reasoning ability is an important ability for students to understand mathematical concepts. Much research has been conducted on this capability, but it is necessary to map existing research to provide a clearer picture of future research topics. This research aims to provide a bibliometric overview of trends in the use of proportional reasoning skills in mathematics teaching research. The method in this research is bibliometric analysis, which aims to analyze and classify bibliographic material by presenting a representative summary of literature in the Scopus database. The search was carried out using the keyword